2014
DOI: 10.1002/acn3.62
|View full text |Cite
|
Sign up to set email alerts
|

Examining dorsal striatum in cognitive effort using Parkinson's disease and fMRI

Abstract: ObjectiveUnderstanding cognition mediated by the striatum can clarify cognitive deficits in Parkinson's disease (PD). Previously, we claimed that dorsal striatum (DS) mediates cognitive flexibility. To refute the possibility that variation in cognitive effort confounded our observations, we reexamined our data to dissociate cognitive flexibility from effort. PD provides a model for exploring DS-mediated functions. In PD, dopamine-producing cells supplying DS are significantly degenerated. DS-mediated functions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
19
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 58 publications
(85 reference statements)
2
19
0
Order By: Relevance
“…We found that DS activity correlates only with decisions and response selections requiring deliberation but not with late‐stage, stimulus–response association learning. Our results challenge the notion that the DS underlies the development of automaticity, integrating rather with a growing literature suggesting that DS—particularly the caudate nucleus—mediates decision making [Cincotta and Seger, ; Little et al, ; Seger et al, ] when an element of deliberation is required [Atallah et al, ; Grahn et al, ; Hiebert et al, ; Jessup and O'Doherty, ; MacDonald et al, ; McDonald and Hong, ; Postle and D'Esposito, ; Smittenaar et al, ].…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…We found that DS activity correlates only with decisions and response selections requiring deliberation but not with late‐stage, stimulus–response association learning. Our results challenge the notion that the DS underlies the development of automaticity, integrating rather with a growing literature suggesting that DS—particularly the caudate nucleus—mediates decision making [Cincotta and Seger, ; Little et al, ; Seger et al, ] when an element of deliberation is required [Atallah et al, ; Grahn et al, ; Hiebert et al, ; Jessup and O'Doherty, ; MacDonald et al, ; McDonald and Hong, ; Postle and D'Esposito, ; Smittenaar et al, ].…”
Section: Discussionsupporting
confidence: 67%
“…Indeed, a reinterpretation of these early‐ and late‐learning experiments, considering the facts that decision making and stimulus–response association learning (a) depend upon one another to produce accurate performance and (b) are often merged in fMRI studies, could integrate two divergent and extensive literatures regarding DS's role in cognition. Increasingly, DS is linked to response selection and decision making [Atallah et al, ; Grahn et al, ; Jessup and O'Doherty, ; MacDonald et al, ]. Decision making is defined as the process of representing and assigning values to different response possibilities, then selecting and executing the most appropriate action [Rangel et al, ].…”
Section: Introductionmentioning
confidence: 99%
“…Despite this, for all participants, no significant interference occurred in Session 3 when stimuli occurred in the location opposite to the spoken “right” or “left” response paired with them in Session 1. Dissociations between facilitation and interference effects in similar paradigms are commonly noted 11,28,30…”
Section: Discussionmentioning
confidence: 94%
“…Classically, the putamen has primarily been considered a motor structure, and abnormal putamen structure and function are closely related to PD . MacDonald et al reported that the dorsal striatum (bulk of the caudate nucleus and the putamen) mediates cognitive flexibility and cognitive effort in PD . The lesser functional connectivity between MrD and putamen demonstrated the network impairment, and supports the hypothesis that MrD contributes to cognitive dysfunction in patients with PD.…”
Section: Discussionmentioning
confidence: 81%